Safety Assessment of Glyphaea brevis Spreng. (Tiliaceae): Acute and Subacute Toxicity of the Leaf Aqueous Extract in Mice and Wistar Rats - Dakam, William; Nguemfo, Edwige Laure; Fannang, Simone Véronique; Azombo, Erika Lionelle Asseng; Ndomou, Mathieu (Journal of Drug Delivery and Therapeutics, 2022)
Background: Despite the various medicinal applications of Glyphaea brevis, no toxicology data are available that could guarantee its safety or describe its possible toxic effects. We studied the acute and subacute toxicity of leaf aqueous extract of G. brevis (GbAE) in animal models. Materials and methods: In acute toxicity study, mice were given a single oral administration of GbAE at doses of 1000, 2000 and 5000 mg/kg body weight (bw). The animals were monitored for behavioral changes and possible mortality over a 48-hour period, thereafter for 14 days. In the subacute toxicity study, rats were administered G. brevis extract at doses of 300, 600 and 1200 mg/kg bw daily, for 28 days. Tissue specimens of the liver and kidneys were subjected to histological examination using standard hematoxylin-eosin staining. An array of hematological (blood cells count and morphology) and biochemical assessments of blood (ALT, AST, urea, uric acid and creatinine) were performed. Results: In acute toxicity study, GbAE at a dose of 5000 mg/kg caused some signs of toxicity and mortality was higher in males than in females. Subacute toxicity study revealed that GbAE at a dose of 1200 mg/kg caused significant increase of lymphocytes rate as well as serum rates of ALT and creatinin. Microscopically, there were slight hepatic and renal tissue inflammation that was reversible. Conclusion: Some caution should be taken when G. brevis leaves are to be administered repetitively for long periods. Additional preclinical toxicological data should be acquired and ascertained over repeated long-term studies. Keywords: Glyphaea brevis, toxicity, histopathology, liver, kidney